Pengaruh Pengeluaran Pemerintah Sektor Pendidikan dan Kesehatan Terhadap Indeks Pembangunan Manusia di Provinsi Sumatera Barat - Azhariah, Tiara; Febrian, Andis (Madani: Jurnal Ilmiah Multidisiplin, 2025)
How the allocation of funds in the education and health sectors influences the HDI in West Sumatra province from an Islamic perspective is an issue that will be discussed in this research. There is a difference between the theory of the influence of education and health sector spending on the human development index and the data that has been obtained, where there is a mismatch between increasing spending and increasing the human development index. This research aims to identify the influence of government spending in the education and health sectors, both partially and simultaneously, on the human development index in West Sumatra province from an Islamic perspective. Literature study is used as a method for collecting data and information. Quantitative research funding was also chosen as the type of this research. BPS and the Directorate General of Finance of West Sumatra Province were used as sources for obtaining secondary data needed in this research. The data analysis technique uses multiple linear regression analysis. Hypothesis testing uses the t test, F test and determination test (R square). This study indicates that government spending in the education and health sectors partially influences the Human Development Index. Meanwhile, government spending in the education and health sectors also has an impact on the human development index for West Sumatra province. The influence of government expenditure variables in the education and health sectors has an influential contribution to the human development index variable of 56.8%. An additional 43.2% is influenced by other variables that were not examined. For example, per capita income.